Varenicline enhances dopamine release facilitation more than nicotine after long-term nicotine treatment and withdrawal - Perez, Xiomara A (BlackWell Publishing Ltd, 2015)
An important factor contributing to the high relapse rates among smokers is nicotine withdrawal symptoms. Multiple studies suggest that decreased dopamine release in nucleus accumbens plays a key role in withdrawal. However, recent reports showed that long-term nicotine exposure itself also decreases accumbal dopamine release, suggesting that additional mechanisms are involved in withdrawal. Here, we used real-time cyclic voltammetry in brain slices containing the nucleus accumbens to further elucidate the changes in dopamine release linked to nicotine withdrawal. Rats received vehicle or nicotine via the drinking water for 2–3 months. Studies assessing the expression of somatic signs in vehicle-treated, nicotine-treated, and 24-h nicotine withdrawn rats showed that nicotine withdrawal led to a significant increase in somatic signs. Subsequent voltammetry studies showed that long-term nicotine decreased single-pulse-stimulated dopamine release via an interaction at α6β2* receptors. Nicotine withdrawal led to a partial recovery in α6β2* receptor-mediated release. In addition, long-term nicotine treatment alone increased dopamine release paired-pulse ratios and this was partially reversed with nicotine removal. We then evaluated the effect of bath-applied nicotine and varenicline on dopamine release. Nicotine and varenicline both decreased single-pulse-stimulated release in vehicle-treated, nicotine-treated, and nicotine withdrawn rats. However, bath-applied varenicline increased paired-pulse ratios to a greater extent than nicotine during long-term nicotine treatment and after its withdrawal. Altogether these data suggest that nicotine withdrawal is associated with a partial restoration of dopamine release measures to control levels and that varenicline's differential modulation of dopamine release may contribute to its mechanism of action.